Determination of gene copy number status in tert and terc among chronic myeloid leukaemia patients resist ant and responsive to imatinib mesylate treatment - Asrari, Zaidatul Shakila Mohamad (2014)
The frontline treatment of chronic phase (CP) chronic myeloid leukaemia (CML) patients is the use of Imatinib Mesylate (IM). A remarkable CP CML (1/3) patients failed to achieve any degree of good response towards IM treatment. Cancer cells express a higher telomerase activity compared to normal cells in various type of cancers; thus amplification of telomerase core components TERT and TERC gene, is a mechanism responsible for up regulation of telomerase activity. We postulate amplification of telomerase genes might be one of the oncogenesis mechanisms in CP CML development and involved in resistance to IM. The aim of this study was to detennine the gene copy number status of TERT and TERC among CML patients who were either resistant or responsive to IM. A total of 63 CML-IM resistant, 63 CML-IM responsive, 30 nonnal controls and 2 cell lines were enrolled in this study. The DNAs were extracted from peripheral blood and cell pellets. TERT and TERC genes copy number amplification were analysed by qPCR assay by conventional (standard curve) and commercialized assay (Taqman® copy number). FISH analysis was done to validate the presence of TERT and TERC genes amplification. We also evaluated the association between patients' age, gender, treatment status and copy number of TERTITERC genes. There was an increase in TERTand TERC mean N values (standard curve method) in both groups of CML (CML-IM resistant 0.75 and 0.82; CML-IM responsive 0.77 and 0.93) compared to nonnal controls (0.62 and 0.60). Mean N of TERT and TERC values between the two groups of CML patients were significantly different from normal controls. There was however no significant difference of mean N TERT and TERC values between CML-IM resistant patients and CML-IM responsive patients. Only one patient (CML-IM responsive) had TERT gene amplification whereas 5 patients had TERC gene amplification (2 CML-IM resistant and 3 CML-IM responsive). Comparing to standard curve method, Taqman® copy number assay detected 6 CML-IM resistant and 11 CML-IM responsive had amplified TERT gene, whilst 5 CML-IM resistant and 4 CML-IM responsive had amplified TERC gene. Almost 80% of TERT and TERC genes amplification status in CML samples analysed by standard curve method have similar outcomes with FISH. There was no clear association between TERTITERC genes amplification and patients' age, gender and their treatment status. Our results showed a low level of TERTITERC genes amplification and lack of statistical significant difference between TERT/TERC amplification in CML-IM resistant and CML-IM responsive patients may not strongly to show that TERTITERC genes amplification were one of the molecular resistance towards IM. We postulate that increment of telomerase activity via amplification of telomerase genes might not have a huge impact on CML patients particularly in drug resistance.